Strawberry is a commercial fruit. It’s Growth and quality is influenced by soil condition, climate, and its self. Irrigation influences soil characteristic, such as: physical, chemical, and microbiological than influence an environment of its growth. this research used drip irrigation method with debit variation and organic matter composition. RCBD was used in this research. Variation of irrigation debit and organic matter composition are the independent variables, whereas dependent variables ar - Afik Hardanto; Asna Mustofa; Sumarni . (Jurnal Keteknikan Pertanian, 2009)
Strawberry is a commercial fruit. It’s Growth and quality is influenced by soil condition, climate, and its self. Irrigation influences soil characteristic, such as: physical, chemical, and microbiological than influence an environment of its growth. this research used drip irrigation method with debit variation and organic matter composition. RCBD was used in this research. Variation of irrigation debit and organic matter composition are the independent variables, whereas dependent variables are C-Organic, N-available, characteristic of soil, and quality of strawberry fruit. Variation of debit irrigation did not significant influence to C-Organic, whereas organic matter composition had significant influence to C-Organic in 63th, 84th, and 105th day of planting. The highest C-Organic content on D3P3 treatment that is 17.92% and the lowest on D2P2 treatment that is 5.19%. Debit of irrigation influence to N-available content in 105th day of planting. The highest N-available content in D3P1 treatment that is 0.88 ppm, whereas the lowest N-available content in D2P3 treatment that is 0.67 ppm. Result of analysis, debit irrigation had significant influence and could increase fruit weight and reduction sugar-content. Organic matter composition had significant influence to increase fruit weight, vitamin C, total of soluble-solid, and reduction sugar-content. Combination of irrigation debit and organic matter composition had significant influence to fruit weight. In the treatment, debit ofirrigation that make good influence to fruit quality is 300 ml/day/polybag and 1:2 ratio of organic matter composition.Keywords: drip irrigation, organic matter, strawberryDiterima: 16 September 2008; Disetujui: 25 Pebruari 2009